Synthesis and characterization of ZnO nanostructures and ZnO/Ni1-xCuxO heterostructures Application to photovoltaics - Guezzoun, Hanane (Universty Of El-oued جامعة الوادي, 2024)
In the present work, we prepared heterojunctions in the form of thin films based on ZnO and NiO, these thin films were deposited by pyrolysis spray technique on glass substrates. The adopted technique is simple, not expensive, it allows for deposition with a controllable property depending on the conditions of preparation. The first objective of this work is the preparation of thin films of ZnO; our interest is on the optimization of the parameters influence as a (molarity and substrate temperature on the physical and optical properties of ZnO thin films. On the other object is the preparation of thin films of NiO and the study of the doping level influence and substrate temperature on the structural, optical and electrical properties. One has used copper as source of dopants; the doping level was varied from 0 to 4% by weight. The structural study of films by XRD showed that all ZnO films obtained are polycrystalline with a hexagonal wurtzite structure and a preferred orientation along the direction (002) and for NiO films, the structure is cubic with a preferred orientation along the direction (111). While the transmission spectra show that this film exhibited a transmission was detected between 45 and 65% in the visible region. Whereas the electrical characterization I(V) was used to determine the electrical parameters of the realized Na and Al codoped NiO thin films, which revealed that the minimum values of Sheet Resistance was registered for Na (2%) and Al (1%). When studying the effect of the deposition temperature of nickel oxide and its doping ratio with copper on the ZnO/Ni1-xCuxO heterojunctions, we observed a significant improvement in the crystallization of zinc oxide, along with the growth and stability of nickel oxide. These changes led to a significant enhancement in the transparency of the junctions, thereby enhancing their optical properties في العمل الحالًي، قمنا بتحضير وصلات غير متجانسة على شكل أغشية رقيقة تعتمد على أكسيد الزنك وأكسيد النيكل، حيث تم ترسيب هذه الأغشية بتقنية الرش عن طريق الانحلال الحراري على ركائز زجاجية. التقنية المعتمدة بسيطة وغير مكلفة، فهًي تسمح بالترسيب بخاصية يمكن التحكم فيها حسب ظروف التحضير. الهدف الأول من هذا العمل هو تحضير أغشية رقٌيقة من أكسيد الزنك؛ ينصب اهتمامنا على تحسين تأثير العوامل مثل: (المولارية ودرجة حرارة الركيزة على الخواص الفيزيائية والبصرية لأغشية أكسيد الزنك الرقٌيقة. وعلى الجانب الآخر هو تحضير الأغشية الرقيقة من أكسيد النيكل ودراسة تأثير مستوى التشويب وتأثير درجة حرارة الركيزة على الخواص التركيبية والضوئية والكهربائية حيث تم استخدام النحاس كمصدر لتشويب، وتراوح مستوى التشويب من 0 إلى 4 % بالوزن. أظهرت الدراسة التركيبية لهذه الأغشية باستخدام تقنية XRD أن جميع أفلام أكسيد الزنك التي تم الحصول عليها هً متعددة البلورات ذات شكل سداسي ببنية الورتزايت واتجاه نمو مفضل على طول الاتجاه (002). أما بالنسبة للأفلام NiO فإن البنية تكون مكعبة مع اتجاه نمو مفضل على طول الاتجاه، (111) بينما تظهر أطياف الإرسال انتقالا تم اكتشافه بين 45 و65 % في المنطقة المرئية. في حين أنه تم استخدام التوصيف الكهربائي I (V) لتحديد المعلمات الكهربائية لأفلام NiO المشوبة مزدوجا ب Na و Al، حيث أظهرت أن أقل قيمة للمقاومة السطحية تم تسجيلها عند نسبة تطعيم Na (2%) وAl (1%) . عند دراسة تأثير درجة حرارة ترسيب أكسيد النيكل و نسبة تطعيمه بالنحاس على الوصلات غير المتجانسة ZnO/Ni1-xCuxO ، لاحظنا تحسنا ملحوظا في تبلور أكسيد الزنك إلى جانب نمو و استقرار أكسيد النيكل. هذه التغيرات أدت إلى تحسين كبير في شفافية الوصلات، مما يعزز من خصائصها البصرية.
في العلوم الدقيقةPhysics of Materialsأطروحة دكتوراه تخصص
Keywords: ZnO; NiO; Cu; Heterojonction; Thin Layers; TCOs; Spray Pyrolysis method; أكسيد الزنك; أكسيد النيكل; النحاس; الوصلات الغير متجانسة; الأغشية الرقيقة; الرش الكيميائي الحراري